2022
DOI: 10.3390/risks10030045
|View full text |Cite
|
Sign up to set email alerts
|

The Volatility of the “Green” Option-Adjusted Spread: Evidence before and during the Pandemic Period

Abstract: The paper is an investigation on the impact of financial markets on the volatility of the green bonds credit risk component, measured by the option-adjusted spread/swap curve (OAS) before and during the pandemic period. To this purpose, after observing the dynamic joint correlations between all the variables, we adopt Exponential and Generalized AutoRegressive Conditional Heteroskedasticity models, putting the OAS as dependent variable. Our main results show that the conditional variance parameters are signifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Due to the fast-growing attention in green bond return as compared to convention bonds, major aspects of the literature have focused on the "Green-bond" and the difference in yield between green and conventional bond [60][61][62][63][64][65], where robust evidence on the "Greenium" exists regarding the lower yield on green bond against conventional bond [66][67][68][69][70][71][72]. In the view of green bond and its impact on environmental performance, the previous studies shed light on the activities of ESG which determined the favorable benefits [73][74][75][76][77][78].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the fast-growing attention in green bond return as compared to convention bonds, major aspects of the literature have focused on the "Green-bond" and the difference in yield between green and conventional bond [60][61][62][63][64][65], where robust evidence on the "Greenium" exists regarding the lower yield on green bond against conventional bond [66][67][68][69][70][71][72]. In the view of green bond and its impact on environmental performance, the previous studies shed light on the activities of ESG which determined the favorable benefits [73][74][75][76][77][78].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pham (2016) conducted the first empirical study on GB volatility and showed higher volatility in the “label GB markets” than in non-label GB. Since then, many studies investigated this segment and exerted the GB as “a risk-alleviating tool” for investors (Gatti & Florio, 2018; Jin et al, 2020; Mensi et al, 2022; Ortolano & Nissi, 2022; Uddin et al, 2022). Other strands of the literature demonstrated the portfolio diversification benefits for various investors (Gianfrate & Peri, 2019; Huynh et al, 2020; Karim & Naeem, 2022; Sohag et al, 2022; Tsagkanos et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%